2020
DOI: 10.1111/trf.15718
|View full text |Cite
|
Sign up to set email alerts
|

The evanescence and persistence of RBC alloantibodies in blood donors

Abstract: BACKGROUND Blood donors represent a healthy population, whose red blood cell (RBC) alloantibody persistence or evanescence kinetics may differ from those of immunocompromised patients. A better understanding of the biologic factors impacting antibody persistence is warranted, as the presence of alloantibodies may impact donor health and the fate of the donated blood product. METHODS Donor/donation data collected from four US blood centers from 2012 to 2016 as part of the Recipient Epidemiology and Donor Evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Red blood cell (RBC) alloantibodies can also fall beneath the level of detection. This is a property known as antibody evanescence which has been found to occur with 35% of alloantibodies in healthy blood donors and can be considered in this case [13].…”
Section: Antibody Titre ≥64mentioning
confidence: 99%
“…Red blood cell (RBC) alloantibodies can also fall beneath the level of detection. This is a property known as antibody evanescence which has been found to occur with 35% of alloantibodies in healthy blood donors and can be considered in this case [13].…”
Section: Antibody Titre ≥64mentioning
confidence: 99%
“…This serious and sometimes fatal complication can be avoided if the pre‐transfusion testing identifies an antibody to the specific antigen and the patient is then transfused RBCs negative for this antigen. Unfortunately, RBC alloantibodies often evanesce to undetectable levels 17‐23 . In one study of alloimmunized patients with SCD, 81% of patients had at least one previously identified antibody that was later not detected because of evanescence 24 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that while some RBC alloantibodies were detected as early as 30‐days post‐transfusion, most new alloantibodies were not detected until 60‐days post‐transfusion, with a few new alloantibodies not being detected until after 100 days 27 . Antibody evanescence has been found to be related to RBC alloantibody antigen specificity and can occur after only a few weeks to years after initial antibody detection 17,18,20,21 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations